Atom-economical group-transfer reactions with hypervalent iodine compounds - Boelke, Andreas; Finkbeiner, Peter; Nachtsheim, Boris J. (Beilstein Journal of Organic Chemistry, 2018)
Hypervalent iodine compounds, in particular aryl-λ3-iodanes, have been used extensively as electrophilic group-transfer reagents. Even though these compounds are superior substrates in terms of reactivity and stability, their utilization is accompanied by stoichiometric amounts of an aryl iodide as waste. This highly nonpolar side product can be tedious to separate from the desired target molecules and significantly reduces the overall atom efficiency of these transformations. In this short review, we want to give a brief summary of recently developed methods, in which this arising former waste is used as an additional reagent in cascade transformations to generate multiple substituted products in one step and with high atom efficiency.
Keywords: atom economy; benziodoxolones; homogeneous catalysis; hypervalent iodine; iodonium salts